2008
DOI: 10.1080/00071660802298328
|View full text |Cite
|
Sign up to set email alerts
|

Immunomagnetic separation and PCR detection ofListeria monocytogenesin turkey meat and antibiotic resistance of the isolates

Abstract: 1. Conventional cultivation and immunomagnetic separation (IMS) cultivation methods were compared for the isolation specificity and sensitivity of L. monocytogenes from turkey meat samples. PCR was used to confirm the isolates. Disc diffusion was performed to determine the antibiotic susceptibility profiles. A total of 180 turkey meat samples collected from markets in Turkey were tested. 2. L. monocytogenes was detected in 23 samples (12.7%) by IMS and conventional cultivation. It was isolated from 16.6% (10/6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 25 publications
4
20
1
Order By: Relevance
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%
“…After assessing all the information from the recovered publications, seventy-eight primary studies [6,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80,81,82,…”
Section: Methodsmentioning
confidence: 99%
“…Antibodies are routinely used as affinity ligands to separate and concentrate the target analyte from sample matrices using paramagnetic beads (PMBs) [31-34] and also as recognition or reporter molecules on immunoassay platforms [31,35,36]. The PMB-captured cells may be presumptively identified by plating them on selective or differential media [37], or their identity may be confirmed by PCR [38,39], flow cytometry [40], or cytotoxicity assay [41]. The use of a biosensor to detect cells captured by immunomagnetic separation (IMS) is an attractive approach due to increased speed, accuracy, and detection of a low number of targets [34,42,43].…”
Section: Introductionmentioning
confidence: 99%
“…In all other papers including this study, concerning the Japanese situation, no resistant isolates were reported. It is considered that ABPC-resistant isolates may be rare in Japan, compared to Turkey [3,4,23] or the U.S. [15,18], although the reasons are unclear.…”
mentioning
confidence: 99%